Paragraph Writing of Academic Texts in an EFL Context - Andi Wirantaka (Journal of Foreign Language Teaching and Learning, 2016)
This study aims to figure out EFL students’ procedure in developing paragraph and difficulties in paragraph writing during academic text accomplisment process. This current study was qualitative reseach which employed interview as the data collection method of the study. The participants of the study were eight students who were writing their skripsi as requirement for their undergraduate degree. The study was conducted in English Education Department of Universitas Muhammadiyah Yogyakarta. The result of the study showed that in developing paragraph of skripsi, students had insufficient efforts on brainstorming, planning and revising. They only concerned about drafting, and editing. Morever, related to the problems in paragraph writing, the students faced difficulties in English word and word choice, grammar, development of main idea, coherence and cohesiveness, effective sentence, and citation.